Ecological potential of jalawure (Tacca leontopetaloides Kuntz) as an alternative food: relationships between plant height and elevational distribution in coastal Garut, West Java - Wardah; Yossa Istiadi; Dolly Priatna (Indonesian Journal of Applied Environmental Studies, 2025)
Jalawure (Tacca leontopetaloides Kuntz) is a starch-rich tuberous plant endemic to coastal ecosystems of West Java. This study investigated its growth potential as an alternative food source, analyzing plant height and spatial distribution relative to elevation in Garut Regency’s southern coast. Nine observation plots (10 m × 25 m) were established perpendicular to the shoreline across three districts. For each plot, plant height, elevation, distance to shoreline, soil properties, and plant density were measured. Statistical analysis (Kruskal–Wallis, Duncan test, and linear regression) revealed significant variation in plant height across habitats (p = 0.017), with optimal growth at moderate elevations (15–20 m asl) and semi-shaded plots. Population densities varied from 440 to 1,400 individuals per hectare, indicating substantial carbohydrate reserves. Elevation gradient accounted for ~30% of height variation. These findings highlight jalawure’s potential role in community food resilience and climate adaptation, particularly in drought-prone coastal zones. Promoting jalawure cultivation under agroforestry or coastal restoration frameworks may strengthen local food security.